2016
DOI: 10.1111/jfpp.12717
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofSpirulina platensison Physicochemical Properties and Viability ofLactobacillus acidophilusof Probiotic UF Feta Cheese

Abstract: The impact of addition of powdered Spirulina platensis on the physicochemical properties and microbiological of cheese containing Lactobacillus acidophilus and Mentha longifolia L. was studied during the refrigerated storage. Cheese starter cultures (1% w/v) and L. acidophilus (2% w/v) was inoculated to the milk together with M. longifolia L. (0.5 and 1% w/v) and S. platensis (0, 0.3, 0.5 and 0.8% w/v). Produced cheeses were stored at 4C for 45 days and microbial, textural and nutritional aspects were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 16 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…It must be kept in mind that S. platensis , like some other algae, favours the growth of lactic acid bacteria over lactic acid production (Niccolai et al ). It has been confirmed that growth promoting compounds including adenine, hypoxanthine, free amino acids, vitamins and γ‐linolenic acid, which are abundant in S. platensis biomass, can boost the proliferation of proteolytic probiotics (Beheshtipour et al ; Mazinani et al ). Also, algal polysaccharides like β‐glucans from Chlorella vulgaris and S. platensis biomass are already recognised as prebiotics (Niccolai et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be kept in mind that S. platensis , like some other algae, favours the growth of lactic acid bacteria over lactic acid production (Niccolai et al ). It has been confirmed that growth promoting compounds including adenine, hypoxanthine, free amino acids, vitamins and γ‐linolenic acid, which are abundant in S. platensis biomass, can boost the proliferation of proteolytic probiotics (Beheshtipour et al ; Mazinani et al ). Also, algal polysaccharides like β‐glucans from Chlorella vulgaris and S. platensis biomass are already recognised as prebiotics (Niccolai et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Akalin et al () found that S. platensis did not significantly influence the survival of Bifidobacterium animalis in probiotic yoghurts. Mazinani et al () utilised S. platensis (0–0.8%) in probiotic UF feta cheese containing L. acidophilus . They reported that S. platensis enhanced L. acidophilus viability significantly compared with samples lacking algae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of spirulina biomass favoured the growth of the bacteria. Several authors (Varga et al 2002;Guldas and Irkin 2010;Beheshtipour et al 2012Beheshtipour et al , 2013Mazinani et al 2016) have tested the effect of spirulina biomass addition to yogurt, cheese, and fermented milk, with positive results, among which included an increase in the number of lactic acid bacteria and improvement of the nutritional quality of the fermented product during storage. However, to the best of our knowledge, the suitability of spirulina biomass as the sole substrate to obtain lactic acid-fermented products has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cheese is one of the high consumed foods and offers benefits over yogurt because of suitable pH, the high concentrate of fat, protein, and solid texture Mazinani, Fadaei, and Khosravi‐Darani (2016). Bacteriologically acidified feta (BAF‐type cheese) is a product in which milk is acidified using starter cultures and the pre‐cheese has the same chemical composition as the final product.…”
Section: Introductionmentioning
confidence: 99%